Bridging Legal Gaps in Indigenous Customary Land Rights: The Urgency of Lex Specialis in Agrarian Law - Endah Pertiwi; Ujang Badru Jaman (JURNAL AKTA, 2026)
This study aims to examine the legal uncertainty surrounding the protection of indigenous peoples’ customary land rights within Indonesian agrarian law, particularly due to the absence of a lex specialis framework. Although the 1945 Constitution and the Basic Agrarian Law (UUPA) formally recognize customary rights (hak ulayat), their implementation remains constrained by sectoral legislation that prioritizes state and corporate interests. This research employed a normative juridical approach by analyzing constitutional provisions, statutory regulations, and relevant court decisions to identify gaps in legal protection. The novelty of this study lies in its integrative analysis of the doctrinal, constitutional, and comparative dimensions of lex specialis in relation to indigenous rights protection. The findings reveal that the absence of a specific legal framework has led to fragmented regulations, inconsistencies in judicial and administrative practices, and persistent legal uncertainty, which in turn contribute to land conflicts, marginalization, and unequal access to natural resources. Comparative insights from Malaysia and the Philippines demonstrate that the existence of specific legislation can strengthen legal recognition while maintaining alignment with national development objectives. This study concludes that the establishment of a lex specialis law is essential to harmonize state law and customary law, ensure constitutional compliance, and enhance legal certainty and social justice for indigenous peoples. Such reform is also necessary to align Indonesia’s legal system with international human rights standards and to support sustainable and inclusive agrarian governance.